Нові відомості про гриби родини Lachnocladiaceae в Україні - Ординець, О.В.; Юрченко, Є.О. (Український ботанічний журнал, 2011)
Приведены данные о первых для территории Украины находках двух представителей семейства Lachnocladiaceae D.A.Reid (Russulales, Basidiomycota)— Dichostereum effuscatum (Cooke et Ellis) Boidin et Lanq. и Scytinostroma hemidichophyticum Pouzar. В результате критического изучения голотипа Corticium portentosum f. duriusculum (Berk. et Broome) Pilát et Bourdot, приводимая А. Пилатом для микофлористического региона Карпатских лесов, была отнесена к Scytinostroma eurasiaticogalactinum Boidin et Lanq. Two members of the family Lachnocladiaceae D.A. Reid (Russulales, Basidiomycota) are firstly reported for Ukraine. They are Dichostereum effuscatum (Cooke et Ellis) Boidin et Lanq. and Scytinostroma hemidichophyticum Pouzar. The critical study of the holotype of Corticium portentosum f. duriusculum (Berk. et Broome) Pilát et Bourdot, which was cited by A.Pilát for Carpathian Forests mycofloristical region, has been carried out. As a result, the taxon was referred to Scytinostroma eurasiaticogalactinum Boidin et Lanq.